Pharmacological chaperones mitigate noise-induced hearing loss by attenuating sustained PERK activation - Ji Won Hong; Hyehyun Min; Soomin Kim; Hyeong Gi Song; Yujin Choi; Chul Hoon Kim; Jinwoong Bok; Heon Yung Gee (Proceedings of the National Academy of Sciences, 2026)
Noise-induced hearing loss (NIHL) can be either temporary or permanent, depending on the intensity and duration of noise exposure. Excessive noise exposure activates various cellular mechanisms in the cochlea, including oxidative stress, immune responses, and apoptosis. Still, the mechanisms underlying hearing recovery after transient threshold shift (TTS) and lack of recovery after permanent threshold shift (PTS), as well as their therapeutic implications for NIHL, remain unknown. In this study, we performed a comparative analysis of longitudinal changes in the cochlear transcriptome of TTS and PTS mouse models. Our analysis revealed that noise-induced ER stress activates the unfolded protein response (UPR). Notably, the protein kinase R-like endoplasmic reticulum kinase (PERK) branch of the UPR returned to baseline levels following TTS but showed sustained activation following PTS. In addition, the proapoptotic factor C/EBP homologous protein (CHOP) was selectively induced in hair cells following PTS. Administering a PERK inhibitor prior to and following noise exposure hindered hearing restoration after TTS, indicating a requirement for PERK activation in hearing recovery. Inhibition of sustained PERK activation via a PERK inhibitor or reduction of CHOP expression via pharmacological chaperones facilitated partial hearing recovery following PTS. Together, these findings provide insight into the mechanisms underlying NIHL and its prevention, highlighting UPR modulation as a promising therapeutic strategy.